Multimedia Interaktif Pengenalan Organ Dalam Tubuh Manusia Untuk Sekolah Menengah Pertama Berbasis Android - Putra, I Komang Alit; Sudiatmika, I Putu Gd Abdi; Putra, I Gede Eka Wiantara (Jurnal Ilmiah Sains Sosial, Kewirausahaan dan Kebudayaan, 2024)
The research focuses on designing and building interactive multimedia introduction to organs in the human body for android-based junior high school. The application can be accessed by users via android smartphones. The problem solved is the need for introductory media and information to provide an introduction to organs in the human body while providing information about organs in the human body, applied in android-based application media. The Multimedia Development Life Cycle model research method is the choice in developing a system which has stages, system analysis to determine system requirements with the results of the system applied to android applications which provide information related to the introduction of organs in the human body accordingly, then system design includes Unified Modeling Language (UML) and system interfaces, the next stage of system implementation is the stage of implementing the system using the Javascript programming language and the React Native library, finally system testing is carried out to ensure quality using the blackbox method to produce suitability for each expected system function. User target testing through a questionnaire to 30 respondents using a Likert scale resulted in a response of 89.3% with the interpretation criteria "Strongly Agree".